Multi‐energy computed tomography and material quantification: Current barriers and opportunities for advancement. Issue 8 (23rd June 2020) - Jacobsen, Megan C.; Thrower, Sara L.; Ger, Rachel B.; Leng, Shuai; Court, Laurence E.; Brock, Kristy K.; Tamm, Eric P.; Cressman, Erik N.K.; Cody, Dianna D.; Layman, Rick R.
Abstract : Computed tomography (CT) technology has rapidly evolved since its introduction in the 1970s. It is a highly important diagnostic tool for clinicians as demonstrated by the significant increase in utilization over several decades. However, much of the effort to develop and advance CT applications has been focused on improving visual sensitivity and reducing radiation dose. In comparison to these areas, improvements in quantitative CT have lagged behind. While this could be a consequence of the technological limitations of conventional CT, advanced dual‐energy CT (DECT) and photon‐counting detector CT (PCD‐CT) offer new opportunities for quantitation. Routine use of DECT is becoming more widely available and PCD‐CT is rapidly developing. This review covers efforts to address an unmet need for improved quantitative imaging to better characterize disease, identify biomarkers, and evaluate therapeutic response, with an emphasis on multi‐energy CT applications. The review will primarily discuss applications that have utilized quantitative metrics using both conventional and DECT, such as bone mineral density measurement, evaluation of renal lesions, and diagnosis of fatty liver disease. Other topics that will be discussed include efforts to improve quantitative CT volumetry and radiomics. Finally, we will address the use of quantitative CT to enhance image‐guided techniques for surgery, radiotherapy and interventions and provide unique opportunities for development of new contrast agents.